Adaptive Soft Robots: Soft Ultrathin Electronics Innervated Adaptive Fully Soft Robots (Adv. Mater. 13/2018). Issue 13 (30th March 2018) - Wang, Chengjun; Sim, Kyoseung; Chen, Jin; Kim, Hojin; Rao, Zhoulyu; Li, Yuhang; Chen, Weiqiu; Song, Jizhou; Verduzco, Rafael; Yu, Cunjiang
Abstract : An inchworm‐like soft robot is illustrated by Cunjiang Yu and co‐workers, who, in article number 1706695, report an adaptive fully soft‐bodied robot that is based on the hybridization of soft artificial muscle and ultrathin deformable sensors and actuators. The soft robot is capable of shape adaptation and gait locomotion in programmable and adaptive sensing‐actuating manners, like an inchworm.